Poland’s tourism image - results of a survey conducted among Austrian students - Hołderna-Mielcarek, Bernadeta (Economics and Business Review, 2004)
The following paper emphasizes the role of tourism image in creating positive perceptions of nations and positioning countries as attractive holiday destinations. Based on an empirical survey of Poland's tourism image conducted among Austrian students in 2003, the paper identifies features and concepts used by young adults in conceptualising a subjective image of an ideal (dream) holiday destination, and subsequently confronts that image with the perception of Poland as a tourist destination. Conclusions drawn from the survey with respect to Poland's tourism image primarily focus on the need to eliminate negative aspects associated with Poland, and on building a strong image based on the natural environment that creates opportunities for contemporary tourism trends such as soft tourism and ecotourism, not forgetting at the same time historic and cultural merits traditionally associated with Poland. (original abstract)